Economic evaluation of 'Return to Country': A remote Australian initiative to address indigenous homelessness. (June 2016) - Kinchin, Irina; Jacups, Susan; Hunter, Gary; Rogerson, Bernadette
Highlights: 'Return to country' (R2C) is a simple, minimal cost program that offers an innovative approach to addressing indigenous homelessness. The R2C program successfully assisted 140 participants and helped to reduce the prevalence of homelessness in a regional center by 9.6%. The total program cost was estimated at 135, 831 or 970 per participant. The analysis revealed that R2C could have major benefits for a community and a substantial positive cost impact for the government. Abstract: Background: An increase in the number of Indigenous homeless persons in Cairns, Northern Australia, prompted the Queensland Police Service (QPS) to commence a pilot 'Return to Country' (R2C) program. The program was designed to assist homeless people who were voluntarily seeking to return to their home communities. This study assesses the costs of running the program and evaluates its net economic impact. Methods: Retrospective uncontrolled cost, cost-effectiveness and cost-offset analyses were undertaken from a societal perspective. All costs were expressed in 2014 AU. Results: The R2C program successfully assisted 140 participants to return home, reducing the prevalence of homelessness in the regional center by 9.6%. The total program cost was estimated as AU 135, 831 or AU 970 per participant. The economic analysis indicated that R2C was value for money, potentially saving AU 2, 714, 460. Limitations of the study included retrospective data collection and no established alternative comparison group. Conclusion: R2C is a relatively simple, minimal cost program, which can be utilized by policy makers to offer one solution to homelessness. This economic evaluation informs the QPS of the effects of the R2C program in order to guide further program initiatives. The R2C model may be applied to assist temporarily stranded Indigenous people in other locations within Australia or internationally to return home. No funding was obtained for conducting this study.